Sialometry and sialochemistry: diagnostic tools for Sjögren's syndrome - Kalk, W (2001)
BACKGROUND—The common occurrence of xerostomia in Sjögren's syndrome (SS) as well as the easy accessibility of saliva supports the use of sialometry and sialochemistry in the diagnosis of SS. Collection and analysis of whole saliva (oral fluid) is currently the routine technique for sialometry, despite the fact that it is rather inaccurate and impure. OBJECTIVE—To assess the value of glandular sialometry and sialochemistry as diagnostic instruments in SS. METHODS—In a group of 100 consecutive patients referred for diagnosis of SS, glandular secretory flow rates and a spectrum of salivary components (sodium, potassium, chloride, calcium, phosphate, urea, amylase, total protein) were assessed. The patients were classified as positive or negative for SS according to the revised European classification criteria. RESULTS—Patients with SS differed clearly from those who tested negative for SS, showing lower submandibular/sublingual (SM/SL) flow rates and an appreciably changed salivary composition of parotid and SM/SL saliva. Besides changes in salivary flow rate and composition, distinct sialometric profiles were observed, characteristic of either early or late salivary manifestation of SS, or of the xerogenic side effects of medication. CONCLUSIONS—Glandular sialometry and sialochemistry are not only useful tools for differentiating SS from other salivary gland disease in clinical practice, but they also have great potential as diagnostic criteria for SS, showing distinct sialometric and sialochemical changes as well as profiles. Being simple, safe (non-invasive), and sensitive (early disease detection), they have three major advantages over other oral tests for SS.